Evaluation of a Pulsed Xenon Ultraviolet Disinfection System for Reduction of Healthcare-Associated Pathogens in Hospital Rooms. (5th January 2015) - Nerandzic, Michelle M.; Thota, Priyaleela; Sankar C., Thriveen; Jencson, Annette; Cadnum, Jennifer L.; Ray, Amy J.; Salata, Robert A.; Watkins, Richard R.; Donskey, Curtis J.
<x content-type="archive" xml:space="preserve">Abstract</x> OBJECTIVE To determine the effectiveness of a pulsed xenon ultraviolet (PX-UV) disinfection device for reduction in recovery of healthcare-associated pathogens. SETTING Two acute-care hospitals. METHODS We examined the effectiveness of PX-UV for killing of Clostridium difficile spores, methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-resistant Enterococcus (VRE) on glass carriers and evaluated the impact of pathogen concentration, distance from the device, organic load, and shading from the direct field of radiation on killing efficacy. We compared the effectiveness of PX-UV and ultraviolet-C (UV-C) irradiation, each delivered for 10 minutes at 4 feet. In hospital rooms, the frequency of native pathogen contamination on high-touch surfaces was assessed before and after 10 minutes of PX-UV irradiation. RESULTS On carriers, irradiation delivered for 10 minutes at 4 feet from the PX-UV device reduced recovery of C. difficile spores, MRSA, and VRE by 0.55±0.34, 1.85±0.49, and 0.6±0.25 log10 colony-forming units (CFU)/cm2, respectively. Increasing distance from the PX-UV device dramatically reduced killing efficacy, whereas pathogen concentration, organic load, and shading did not. Continuous UV-C achieved significantly greater log10CFU reductions than PX-UV irradiation on glass carriers. On frequently touched surfaces, PX-UV significantly reduced the frequency of positive C. difficile, VRE, and MRSA culture results. CONCLUSIONS The PX-UV device reduced recovery of MRSA, C. difficile, and VRE on glass carriers and on frequently touched surfaces in hospital rooms with a 10-minute UV exposure time. PX-UV was not more effective than continuous UV-C in reducing pathogen recovery on glass slides, suggesting that both forms of UV have some effectiveness at relatively short exposure times. Infect Control Hosp Epidemiol 2014;00(0): 1–6